Modeling the relationship between digital nativity and Smartphone usage in learning English as a foreign language contexts - Hui, Lianghong; Teng, Lin Sophie; Guo, Fangfang (Frontiers in Psychology, 2023)
Introduction Despite many studies exploring the application of digital devices in foreign language learning, only some have investigated the influencing mechanisms of digital nativity on Smartphone usage in this increasingly seamless learning environment. This research aims to explore the relationships between college students’ digital nativity and their use of Smartphones for English learning. Methods The data were collected from 502 undergraduates in mainland China through self-reported questionnaires, namely the Digital Natives Assessment Scale and the Smartphone Use in Learning Foreign Language Scale. Results and Discussion The confirmatory factor analysis validated a four-factor measurement model of digital nativity, including “grow up with technology”, “comfortable with multitasking”, “reliant on graphics for communication” and “thrive on instant gratification and rewards”. A second-order measurement construct of favorable Smartphone usage and its first-order adverse effects in foreign language learning were also examined, demonstrating good validity and reliability. Structural equation modeling analysis revealed that students who displayed more attributes of “grow up with technology” and “thrive on instant gratifications and rewards” tended to adopt smartphones positively for English learning. In addition, those who were more familiar with technological assistance might suffer less from the adverse effects of Smartphone usage. However, the preference for immediate responses and feedback could also lead to more adverse effects when using Smartphones for English learning. Besides, “comfortable with multitasking” and “reliant on graphics for communication” didn’t have any significant predictive impact on either the favorable functions or the adverse effects of Smartphone usage. Based on the research results, we discuss the theoretical and practical implications.